Francisco Xavier de Meneses, IV Conde da Ericeira: O raiar das "Luzes" entre fastos barrocos - Carlota Miranda Urbano (Documentos, 2019)
This opuscule recalls in broad traces a prestigious figure of our cultural history - D. Francisco Xavier de Meneses, IV Conde da Ericeira - undeservedly forgotten: this aristocrat, who polarized in his vise for nearly three decades the aristocracy of Lisbon, effectively played a relevant role in modernising our mindset, documented, among other aspects, by the renewed impulse that gave the literary and scientific activity of numerous academies to which it was connected. Located between two "times", the IV Conde da Ericeira, framed by the Baroque tradition, as it becomes visible in its unpublished text that we know here, it ca nevertheless be considered a pioneer of the "Lights" between us.